DIGITAL LENDING, HOUSEHOLD DEBT, AND FINANCIAL VULNERABILITY EVIDENCE FROM INDONESIA - Zikrillah; Luthfiar Ramiady; Mukhtaruddin (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2026)
Digital lending has rapidly expanded financial inclusion in Indonesia while simultaneously raising concerns over rising household indebtedness and financial vulnerability. Despite growing empirical attention, existing studies primarily examine individual borrowers and rarely distinguish between licensed fintech lending and illegal online lending, leaving the household as the fundamental economic decision-making unit largely unexplored. This study develops a dual-channel model of digital lending-induced household financial vulnerability by integrating behavioral and structural perspectives within a unified analytical framework. Using a cross-sectional household survey complemented by secondary data from the Financial Services Authority (OJK) and Statistics Indonesia (BPS), the study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) with mediation, moderation, and robustness analyses to examine the relationships among digital lending exposure, household debt structure, behavioral propensity, digital financial literacy, and financial vulnerability. The proposed framework distinguishes between legal and illegal digital lending while incorporating household-level behavioral and institutional mechanisms that have received limited attention in previous research. The empirical findings are expected to clarify whether digital lending exposure increases household financial vulnerability through both behavioral and structural pathways, whether digital financial literacy exerts a nonlinear moderating effect, and whether illegal digital lending generates significantly greater financial vulnerability than licensed fintech lending. The study contributes to the household debt literature by extending multidimensional financial vulnerability theory to a fintech-dominated emerging economy and provides policy implications for strengthening macroprudential surveillance through household-level debt monitoring and differentiated regulatory interventions targeting both legal and illegal digital lending markets.